Outdoor anti-aging plastic composite material and preparation method thereof
By using a combination of modified anti-aging agents and reinforced fillers in plastic materials, the problem of plastic materials being prone to aging and cracking is solved, significantly improving its aging resistance and UV resistance, and extending its service life.
Patent Information
- Application Number
- CN202411312590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The quality of the plastic runway materials on the market is unstable, the anti-aging performance is poor, and it is prone to aging and cracking, resulting in a reduced service life.
Using a combination of rubber and plastic elastomer, modified anti-aging agent and reinforced filler, intermediate products are generated by the reaction of melamine, allyl isothiocyanate and epoxychlorohydrin in the modified anti-aging agent, and γ-aminopropyl tri Ethoxysilane modifies nanocellulose, combines nanotitanium dioxide and calcium carbonate to prepare reinforced fillers to improve the aging resistance of the material.
It significantly improves the aging resistance of plastic composite materials, avoids the migration and precipitation of anti-aging agents, extends the material life, and improves the resistance to ultraviolet and mechanical properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic materials, and in particular to an outdoor aging-resistant plastic composite material and a preparation method thereof. Background Art
[0002] Plastic composite materials are elastomers prepared by blending plastics and rubber, and the particles are obtained by extrusion granulation or crushing granulation. At present, plastic particles have been widely used as indispensable components in sports venues, home appliances, automobiles, mobile phones, PCs, medical equipment, and lighting appliances. In plastic tracks, plastic particles can be mixed with adhesives and spread into plastic venues. In artificial turf, the filling of plastic particles increases the elasticity of the turf and can cushion the impact of athletes on the ground. At present, many runway particles on the market are mostly made of EPDM rubber. In order to reduce costs, a large amount of plasticizers and fillers are added. However, the quality of plastics on the market is unstable, and the anti-aging performance is not good. After adding antioxidants and other additives, it is easy to precipitate and migrate, which makes the plastic easy to age, crack, and reduce the service life. Therefore, a plastic with good anti-aging performance is very promising in the market. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides an outdoor aging-resistant plastic composite material and a preparation method thereof.
[0004] The purpose of the present invention can be achieved through the following technical solutions: An outdoor aging-resistant plastic composite material comprises the following raw materials in parts by weight: 100 parts of rubber-plastic elastomer, 2-5 parts of stabilizer, 25-35 parts of plasticizer, 60-100 parts of reinforcing filler, and 2-4 parts of modified antioxidant; The rubber-plastic elastomer is obtained by blending EPDM rubber, ethylene-vinyl acetate copolymer and chlorinated polyethylene, and the sum of the masses of the three is 100 parts; Furthermore, the rubber-plastic elastomer comprises 20-50 parts of EPDM rubber, 40-70 parts of ethylene-vinyl acetate copolymer, and 10-40 parts of chlorinated polyethylene; The modified antioxidant is prepared by the following steps: Step A1, add melamine to ethanol and disperse it evenly, then add dibutyltin dilaurate, and slowly add allyl isothiocyanate under stirring conditions, increase the system temperature to 45-55° C., stir the reaction for 3.5-4.5 hours, and filter to obtain intermediate product 1; Step A2, adding sodium hydroxide and ethanol to the intermediate product 1 and stirring to disperse, then adding epichlorohydrin to react for 2-3 hours, distilling under reduced pressure, then slowly dropping 25wt% sodium hydroxide solution, and heating to 60-70°C to react for 2-3 hours, filtering, washing, and drying to obtain the intermediate product 2; Step A3, dispersing γ-aminopropyltriethoxysilane in an ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjusting the pH to 8-9, adding nanocellulose and ultrasonically treating for 10-20 minutes, stirring and reacting for 2-3 hours, adding intermediate product 2, and refluxing at 65-75° C. under nitrogen for 24-48 hours, centrifuging, washing, and drying to obtain a modified antioxidant; Further, in step A1, the usage ratio of melamine, ethanol, dibutyltin dilaurate and allyl isothiocyanate is 0.01-0.03 mol: 100 mL: 0.001-0.005 g: 0.02-0.06 mol; Further, the usage ratio of sodium hydroxide, ethanol, epichlorohydrin, sodium hydroxide solution in step A2 and melamine in step A1 is 0.04-0.06 g: 50 mL: 0.015-0.035 mol: 10-15 mL: 0.01-0.03 mol; Furthermore, in step A3, the volume ratio of γ-aminopropyltriethoxysilane, ethanol solution, nanocellulose and intermediate product 2 is 0.5-2 g: 100 mL: 1-3 g: 0.2-1 g.
[0005] The reinforcing filler is prepared by the following steps: adding nano titanium dioxide to a 0.2-2 mol / L sodium carbonate solution and stirring evenly, then slowly adding a 0.5-4 mol / L calcium chloride solution and stirring for 5-10 minutes, filtering, washing, and then precipitating in deionized water for 24 hours, filtering, and drying to obtain the reinforcing filler; Furthermore, the dosage ratio of nano titanium dioxide, sodium carbonate solution, calcium chloride solution and deionized water in the reinforcing filler is 1-3g: 50-100mL: 100-200mL: 100mL.
[0006] A method for preparing an outdoor aging-resistant plastic composite material comprises the following steps: Step S1, weighing the raw materials by weight, putting the rubber-plastic elastomer into an internal mixer, and then adding a stabilizer, a reinforcing filler, a plasticizer and a modified antioxidant in sequence, mixing at 100-150° C. for 8-12 minutes, discharging the material, and discharging the material to obtain a mixed rubber; Step S2, transferring the mixed rubber to an open mixer, refining, sheeting, and then extruding in an extruder to obtain a rubber sheet; Step S3, irradiating and cross-linking the rubber sheet, cutting and crushing the rubber sheet to obtain a plastic composite material.
[0007] Beneficial effects of the present invention: The plastic composite material prepared by the present invention is based on a rubber-plastic elastomer as a matrix, and various additives are added to improve the aging resistance of the plastic composite material; wherein the addition of modified antioxidants and reinforcing fillers not only improves the aging resistance of the matrix, but also avoids the decline of aging resistance due to migration and precipitation.
[0008] In the modified antioxidant, -NH2 in melamine and -N=C=S in allyl isothiocyanate are first reacted to generate intermediate product 1; then the epoxy group in epichlorohydrin and the amino group in intermediate product 1 undergo a ring-opening reaction, and under alkaline conditions, the chloromethyl and hydroxyl groups in the product react to generate new epoxy groups to obtain intermediate product 2; finally, the nanocellulose is modified with a silane coupling agent, and the intermediate product 2 is grafted onto the nanocellulose to obtain a modified antioxidant. The addition of modified antioxidants can significantly improve the anti-aging performance of the matrix. This is because the amino compounds and triazine structures contained in the modified antioxidants can effectively remove free radicals, inhibit the free radical chain reaction, and delay the aging of the matrix caused by the external environment, thereby improving the life of the matrix; the carbon-carbon double bond structure it contains can combine with the rubber and plastic elastomer molecules during the vulcanization process, fix the antioxidant molecules on the rubber and plastic molecular chains, and greatly limit the movement of the antioxidant molecules, thereby making the antioxidant's volatility and migration resistance better, improving the "frost" phenomenon of the matrix, reducing migration in the matrix, and more continuously exerting anti-aging ability; the antioxidant can weaken the interaction between the active groups of the filler, prevent intermolecular attraction and aggregation, thereby promoting the dispersion of the filler and further improving the anti-aging performance; the thiourea structure it contains can also be used as a vulcanization accelerator, which can accelerate the vulcanization rate and reduce the energy consumption in the vulcanization process; in addition, the introduction of nanocellulose also improves the mechanical properties of the plastic matrix.
[0009] The addition of reinforcing fillers improves the UV resistance of the matrix, thereby improving the matrix's aging resistance outdoors. Titanium dioxide, due to its own characteristics, can absorb and scatter ultraviolet light entering the film layer, converting light energy into heat energy and then consuming ultraviolet light, avoiding aging caused by ultraviolet light; and the coating of calcium carbonate can reduce the production cost of the matrix while improving the mechanical properties of the matrix. DETAILED DESCRIPTION
[0010] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0011] The modified antioxidant is prepared by the following steps: Step A1, add 0.01 mol of melamine to 100 mL of ethanol and disperse evenly, then add 0.001 g of dibutyltin dilaurate, and slowly add 0.02 mol of allyl isothiocyanate under stirring conditions, raise the system temperature to 45° C., stir and react for 3.5 hours, filter, and obtain intermediate 1; Step A2, add 0.04 g of sodium hydroxide and 50 mL of ethanol to the intermediate product 1, stir and disperse, then add 0.015 mol of epichlorohydrin to react for 2 h, distill under reduced pressure, then slowly dropwise add 10 mL of 25 wt% sodium hydroxide solution, and heat to 60 ° C to react for 2 h, filter, wash and dry to obtain the intermediate product 2; Step A3, disperse 0.5g of γ-aminopropyltriethoxysilane in 100mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 8, add 1g of nanocellulose, ultrasonicate for 10min, react with stirring for 2h, add 0.2g of intermediate product 2, reflux at 65°C under nitrogen for 24h, centrifuge, wash and dry to obtain the modified antioxidant.
[0012] The reinforced filler is prepared by the following steps: Add 1g of nano titanium dioxide into 50mL of 0.2mol / L sodium carbonate solution and stir evenly, then slowly add 100mL of 0.5mol / L calcium chloride solution and stir to react for 5min, filter and wash, then precipitate in 100mL of deionized water for 24h, filter and dry to obtain the reinforced filler. Example
[0013] The modified antioxidant is prepared by the following steps: Step A1, add 0.02 mol of melamine to 100 mL of ethanol and disperse evenly, then add 0.003 g of dibutyltin dilaurate, and slowly add 0.04 mol of allyl isothiocyanate under stirring conditions, raise the system temperature to 50° C., stir and react for 4 hours, filter, and obtain intermediate 1; Step A2, add 0.05 g of sodium hydroxide and 50 mL of ethanol to the intermediate product 1, stir and disperse, then add 0.025 mol of epichlorohydrin to react for 2.5 h, distill under reduced pressure, then slowly dropwise add 12 mL of 25 wt% sodium hydroxide solution, and heat to 65 ° C to react for 2.5 h, filter, wash and dry to obtain the intermediate product 2; Step A3, disperse 1 g of γ-aminopropyltriethoxysilane in 100 mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 8.5, add 2 g of nanocellulose, ultrasonicate for 15 min, react with stirring for 2.5 h, add 0.5 g of intermediate product 2, reflux at 70 ° C under nitrogen for 36 h, centrifuge, wash and dry to obtain the modified antioxidant.
[0014] The reinforced filler is prepared by the following steps: Add 2g of nano titanium dioxide into 80mL of 1mol / L sodium carbonate solution and stir evenly, then slowly add 150mL of 2mol / L calcium chloride solution and stir to react for 8min, filter and wash, then precipitate in 100mL of deionized water for 24h, filter and dry to obtain the reinforced filler. Example
[0015] The modified antioxidant is prepared by the following steps: Step A1, add 0.03 mol of melamine to 100 mL of ethanol and disperse evenly, then add 0.005 g of dibutyltin dilaurate, and slowly add 0.06 mol of allyl isothiocyanate under stirring conditions, raise the system temperature to 55° C., stir and react for 4.5 hours, filter, and obtain intermediate 1; Step A2, add 0.06 g of sodium hydroxide and 50 mL of ethanol to the intermediate product 1, stir and disperse, then add 0.035 mol of epichlorohydrin to react for 3 h, distill under reduced pressure, then slowly dropwise add 15 mL of 25 wt% sodium hydroxide solution, and heat to 70 ° C to react for 3 h, filter, wash and dry to obtain the intermediate product 2; Step A3, disperse 2g of γ-aminopropyltriethoxysilane in 100mL of ethanol solution (the volume ratio of ethanol to deionized water is 9:1), adjust the pH to 9, add 3g of nanocellulose, ultrasonicate for 20min, react with stirring for 3h, add 1g of intermediate product 2, reflux at 75°C under nitrogen for 48h, centrifuge, wash and dry to obtain the modified antioxidant.
[0016] The reinforced filler is prepared by the following steps: Add 3g of nano titanium dioxide into 100mL of 2mol / L sodium carbonate solution and stir evenly, then slowly add 200mL of 4mol / L calcium chloride solution and stir for 10min, filter and wash, then precipitate in 100mL of deionized water for 24h, filter and dry to obtain the reinforced filler. Example
[0017] A method for preparing an outdoor aging-resistant plastic composite material comprises the following steps: 100 parts of rubber-plastic elastomer, 2 parts of stabilizer (calcium-zinc composite stabilizer), 25 parts of plasticizer (paraffin oil), 60 parts of the reinforcing filler prepared in Example 1, and 2 parts of the modified antioxidant prepared in Example 1; Further, the rubber-plastic elastomer is obtained by blending 20 parts of EPDM rubber, 40 parts of ethylene-vinyl acetate copolymer and 40 parts of chlorinated polyethylene; Step S1, weighing the raw materials by weight, putting the rubber-plastic elastomer into an internal mixer, and then sequentially adding a stabilizer (calcium-zinc composite stabilizer), the reinforcing filler prepared in Example 1, a plasticizer (paraffin oil) and the modified antioxidant prepared in Example 1, mixing at 100° C. for 8 minutes, discharging the material, discharging the material under the sheet, and obtaining a mixed rubber; Step S2, transferring the mixed rubber to an open mixer, refining, sheeting, and then extruding in an extruder to obtain a rubber sheet; Step S3, irradiating and cross-linking the rubber sheet, cutting and crushing the rubber sheet to obtain a plastic composite material. Example
[0018] A method for preparing an outdoor aging-resistant plastic composite material comprises the following steps: 100 parts of rubber-plastic elastomer, 3 parts of stabilizer (calcium-zinc composite stabilizer), 30 parts of plasticizer (paraffin oil), 80 parts of the reinforcing filler prepared in Example 2, and 3 parts of the modified antioxidant prepared in Example 2; Further, the rubber-plastic elastomer is obtained by blending 30 parts of EPDM rubber, 50 parts of ethylene-vinyl acetate copolymer and 20 parts of chlorinated polyethylene; Step S1, weighing the raw materials by weight, putting the rubber-plastic elastomer into an internal mixer, and then sequentially adding a stabilizer (calcium-zinc composite stabilizer), the reinforcing filler prepared in Example 2, a plasticizer (paraffin oil) and the modified antioxidant prepared in Example 2, mixing at 130° C. for 10 min, discharging the material, discharging the material under the sheet, and obtaining a mixed rubber; Step S2, transferring the mixed rubber to an open mixer, refining, sheeting, and then extruding in an extruder to obtain a rubber sheet; Step S3, irradiating and cross-linking the rubber sheet, cutting and crushing the rubber sheet to obtain a plastic composite material. Example
[0019] A method for preparing an outdoor aging-resistant plastic composite material comprises the following steps: 100 parts of rubber-plastic elastomer, 5 parts of stabilizer (calcium-zinc composite stabilizer), 35 parts of plasticizer (paraffin oil), 100 parts of the reinforcing filler prepared in Example 3, and 2-4 parts of the modified antioxidant prepared in Example 3; Further, the rubber-plastic elastomer is obtained by blending 50 parts of EPDM rubber, 40 parts of ethylene-vinyl acetate copolymer and 10 parts of chlorinated polyethylene; Step S1, weighing the raw materials by weight, putting the rubber-plastic elastomer into an internal mixer, and then sequentially adding a stabilizer (calcium-zinc composite stabilizer), the reinforcing filler prepared in Example 3, a plasticizer (paraffin oil) and the modified antioxidant prepared in Example 3, mixing at 150° C. for 12 minutes, discharging the material, and discharging the material to obtain a mixed rubber; Step S2, transferring the mixed rubber to an open mixer, refining, sheeting, and then extruding in an extruder to obtain a rubber sheet; Step S3, irradiating and cross-linking the rubber sheet, cutting and crushing the rubber sheet to obtain a plastic composite material.
[0020] Comparative Example 1 This comparative example is a plastic composite material, which is different from Example 6 in that titanium dioxide is used instead of the reinforcing filler prepared in Example 3, and the rest is the same.
[0021] Comparative Example 2 This comparative example is a plastic composite material, which is different from Example 6 in that antioxidant 1010 is used instead of the modified antioxidant prepared in Example 3, and the rest is the same.
[0022] The plastic composite materials prepared in Examples 4-6 and Comparative Examples 1-2 were injection molded into dumbbell-shaped specimens at 150° C., and the aging resistance test was performed on the dumbbell-shaped specimens.
[0023] UV aging performance test: The tensile strength and elongation at break of the sample are tested before aging, and then the sample is placed in a xenon aging test box for 400 hours and then the tensile performance and elongation at break are tested. The box radiates 290-340nm ultraviolet rays, with a rated power of 1.8kW, a temperature of (60±3)℃, and a relative humidity of (50±5)%; Thermal aging performance test: Place the sample in an aging box at (85±3)℃ and heat it continuously for 5 days under forced ventilation conditions. Test the tensile properties and elongation at break of the thermally aged sample. According to GB / T 528-2009, use a universal testing machine to test the tensile strength and elongation at break of dumbbell-shaped tensile specimens. The test results are shown in the following table:
[0024] It can be seen from the above table that the plastic composite material prepared by the present invention is subjected to the ultraviolet aging performance test and the heat aging performance test and then the tensile performance test, indicating that it has excellent aging resistance and can therefore be widely used outdoors.
[0025] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. An outdoor aging-resistant plastic composite material, characterized in that: The raw materials include the following parts by weight: 100 parts of rubber and plastic elastomer, 2-5 parts of stabilizer, 25-35 parts of plasticizer, 60-100 parts of reinforcing filler, and 2-4 parts of modified antioxidant; The rubber-plastic elastomer is obtained by blending EPDM rubber, ethylene-vinyl acetate copolymer and chlorinated polyethylene, and the sum of the masses of the three is 100 parts; The modified antioxidant is prepared by the following steps: Step A1, add melamine to ethanol and disperse it evenly, then add dibutyltin dilaurate, and slowly add allyl isothiocyanate under stirring conditions, increase the system temperature to 45-55° C., stir the reaction for 3.5-4.5 hours, and filter to obtain intermediate product 1; Step A2, adding sodium hydroxide and ethanol to the intermediate product 1 and stirring to disperse, then adding epichlorohydrin to react for 2-3 hours, distilling under reduced pressure, then slowly dropping 25wt% sodium hydroxide solution, and heating to 60-70°C to react for 2-3 hours, filtering, washing, and drying to obtain the intermediate product 2; Step A3, disperse γ-aminopropyltriethoxysilane in an ethanol solution, adjust the pH to 8-9, add nanocellulose, ultrasonicate for 10-20 minutes, react with stirring for 2-3 hours, add intermediate 2, and reflux at 65-75°C under nitrogen for 24-48 hours, centrifuge, wash and dry to obtain a modified antioxidant.
2. The outdoor aging-resistant plastic composite material according to claim 1, characterized in that: The rubber and plastic elastomer contains 20-50 parts of EPDM rubber, 40-70 parts of ethylene-vinyl acetate copolymer and 10-40 parts of chlorinated polyethylene.
3. The outdoor aging-resistant plastic composite material according to claim 1, characterized in that: In step A1, the usage ratio of melamine, ethanol, dibutyltin dilaurate and allyl isothiocyanate is 0.01-0.03 mol:100 mL:0.001-0.005 g:0.02-0.06 mol.
4. The outdoor aging-resistant plastic composite material according to claim 1, characterized in that: The usage ratio of sodium hydroxide, ethanol, epichlorohydrin, sodium hydroxide solution in step A2 and melamine in step A1 is 0.04-0.06 g:50 mL:0.015-0.035 mol:10-15 mL:0.01-0.03 mol.
5. The outdoor aging-resistant plastic composite material according to claim 1, characterized in that: The volume ratio of γ-aminopropyltriethoxysilane, ethanol solution, nanocellulose and intermediate product 2 in step A3 is 0.5-2 g: 100 mL: 1-3 g: 0.2-1 g.
6. The outdoor aging-resistant plastic composite material according to claim 1, characterized in that: The reinforcing filler is prepared by the following steps: adding nano titanium dioxide to a 0.2-2 mol / L sodium carbonate solution and stirring evenly, then slowly adding a 0.5-4 mol / L calcium chloride solution and stirring for 5-10 minutes, filtering, washing, and then precipitating in deionized water for 24 hours, filtering, and drying to obtain the reinforcing filler.
7. The outdoor aging-resistant plastic composite material according to claim 6, characterized in that: The dosage ratio of nano titanium dioxide, sodium carbonate solution, calcium chloride solution and deionized water in the reinforcing filler is 1-3g: 50-100mL: 100-200mL: 100mL.
8. The method for preparing an outdoor aging-resistant plastic composite material according to claim 1, characterized in that: The following steps are involved: Step S1, weighing the raw materials by weight, putting the rubber-plastic elastomer into an internal mixer, and then adding a stabilizer, a reinforcing filler, a plasticizer and a modified antioxidant in sequence, mixing at 100-150° C. for 8-12 minutes, discharging the material, and discharging the material to obtain a mixed rubber; Step S2, transferring the mixed rubber to an open mixer, refining, sheeting, and then extruding in an extruder to obtain a rubber sheet; Step S3, irradiating and cross-linking the rubber sheet, cutting and crushing the rubber sheet to obtain a plastic composite material.
Citation Information
Patent Citations
Oilproof cabtyre insulation material
CN101575434A
Preparation method of high-elastic environment-friendly plastic runway particles
CN107880412A
Anti-aging water-stop belt and preparation method thereof
CN112662083A
Thermo-oxidative aging resistant PVC (polyvinyl chloride) rubber material and preparation method thereof
CN118027580A
Flame-retardant ethylene propylene diene monomer composition and hose thereof
CN118440454A